How Are English-speaking Children in Quebec Doing? - Community Health and Social Services Network (CHSSN) (ESDC Dialogue Day, 2024)

La situation des enfants d'expression anglaise au Québec - Community Health and Social Services Network (CHSSN) (Journée de dialogue d’EDSC, 2024)

Championing Early Literacy Through Libraries and Community Partnerships - Dixit, Aisha (QUESCREN Education and Vitality Forum 2023, 2023)

The QFHSA Supports Bill S-251 : An Act to Repeal Section 43 of the Criminal Code (Truth and Reconcilliation Commission of Canada's Call to Action Number 6) - Quebec Federation of Home and School Associations (QFHSA) (2023)

Learning Landscapes Journal : Education in a Pivotal Time : The Moment for Inspiration, Innovation, and Change - Leading English Education and Resource Network (LEARN) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Resolution 2023-08 : Accomodate Immigrant and Refugee Children - Quebec Federation of Home and School Associations (QFHSA) (2023)

What the Community School Approach Brings to Quebec's English School Sector: Connections, Connections, Connections - Horrocks, Debbie; Loomer, Benjamin; Lamarre, Patricia (Lunch & Learn, 2022)

Welcome to Kindergarten : Information for Parents / Bievenue à la maternelle : Information aux parents - Jeffery Hale - Saint Brigid's (JHSB) (2022)

Outil de référence pour venir en aide aux enfants et aux familles d’expression anglaise vulnérables / Reference Tool for Reaching Vulnerable English-speaking Children and Families - Community Health and Social Services Network (CHSSN) (2022)

Comment les parents d'expression anglaise vivent-ils les services au Québec? - Community Health and Social Services Network (CHSSN) (2021)

KIDS Summer Camp 2021 : Final Report - Maurice, Jenna (Coasters Association, 2021)
The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation.

New Case-MCQ Program Provides Free Monthly Books to Young Readers - Ottier, Audrey; Vidal, Emily (2021)

Early Childhood Session - Cech, Anne-Marie (Montreal Community Forum, 2021)

Early Childhood Resource Guide: Matapedia to Shigawake : 2021 - Committee for Anglophone Social Action (CASA) (2021)

English Language Early Childhood Services : Opinion survey among English-speaking Parents in Quebec - Community Health and Social Services Network (CHSSN) (2021)

Services à la petite enfance en anglais : Sondage d’opinion mené auprès de parents anglophones résidant au Québec - Community Health and Social Services Network (CHSSN) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

In celebration of Early Childhood Week, the Community Health and Social Services Network is pleased to present : Supporting the Well-being of Young Children in English-speaking Communities! - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Soutenir les enfants et les familles anglophones de la Côte-Nord du Québec - L'Association communautaire de la Côte-Nord (ACCN) (Community Health and Social Services Network (CHSSN), 2020)

Supporting English-speaking Children and Families on the North Shore of Quebec - North Shore Community Association (NSCA) (Community Health and Social Services Network (CHSSN), 2020)

Directory of Resources : Early childhood / Bottin des ressources : petite enfance - NDG Community Council (NDGCC) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Services d'éducation spécialisé pour parents d'enfants de 0 à 16 ans - Jeffery Hale - Saint Brigid's (JHSB) (2019)

Van-Seasons - Quebec Writers' Federation (QWF) (2019)

2019 Final Report - Keats, Shannon A. (Coasters Association, 2019)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. From 2008 to 2016 the five camps were in operation and ran very well. This year (2019), the community committee in Blanc Sablon made the decision to run the KIDS Summer camp in Blanc Sablon through the Municipality of Blanc Sablon with minor support from the Coasters Association in terms of advice and documentation.

Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)

Selected Characteristics of Laval's English-speaking Children 0-5 - Pocock, Joanne (2019)

Soutenir les enfants et les familles anglophones en Gaspésie et aux Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings est une approche adaptée pour aider les enfants et les familles d’expression anglaise de la Gaspésie et des Îles-de-la-Madeleine. L’initiative est née d’une collaboration entre CASA, CAMI et VGPN, qui ont commencé à travailler avec des partenaires régionaux et locaux pour mieux adapter les programmes et les services afin de soutenir les enfants d’expression anglaise de 0 à 5 ans et leurs familles. Le Réseau communautaire de santé et de services sociaux (RCSSS) a adopté cette approche comme cadre de référence provinciale pour les communautés d’expression anglaise.

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings is an adapted approach to supporting English-speaking children and families in the Gaspé and Magdalen Islands. It originated through a collaboration between CASA, CAMI and VGPN who began to work with regional and local partners to better adapt programs and services to support English- speaking children 0 to 5 years old and their families. This approach has been adopted by the CHSSN as a provincial framework for English- speaking communities.

I Am Me : Mini Mag - Vision Gaspé-Percé Now (2019)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2019)

Who Are Our 0-5 year Olds? : A Portrait of English-speaking 0-5 Year Olds in the Outaouais Region WHO AREOER - Connexions Resource Centre (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

2018 Kids Summer Camp - Fequet Griffin, Priscilla (Coasters Association, 2018)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. From 2008 to 2016 the five camps were in operation and ran very well.

Haiku Counting Book - Quebec Writers' Federation (QWF) (2018)

Waves - Quebec Writers' Federation (QWF) (2018)

An Adapted Approach to Supporting English-Speaking Children (0-5) and Families in the Province of Quebec - Community Health and Social Services Network (CHSSN) (2018)
The primary objective of this document is to further encourage and inspire English-speaking communities to collaborate with stakeholders in their regions offering programs and services to children and families. The document may also serve as a useful tool for stakeholders to become more aware of specific needs often faced by Englishspeaking children and their families and learn about some of the adapted approaches and initiatives underway.

I Am Me : Mini Mag - Vision Gaspé-Percé Now (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

Travellin' Toddler Time : 2018-2019 Schedule - Voice of English-speaking Quebec (VEQ) (2018)

KIDS Summer Camp 2017 - Keats, Shannon A. (Coasters Association, 2017)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. From 2008 to 2016 the five camps were in operation and ran very well.

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

KIDS Summer Camp - Keats, Shannon A. (Coasters Association, 2016)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010, 2011 and 2012, 2013, 2014, 2015 the five camps were in operation and ran very well.

Your Child's Health : Children and Sleep - Jeffery Hale - Saint Brigid's (JHSB) (2016)

Children 0 to 5 and their Parents : Québec, 2016 - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Chaudière-Appalaches - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Abitibi-Témiscamingue - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Est-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Estrie – CHU de Sherbrooke - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Ouest-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Outaouais - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Capitale-Nationale - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Côte-Nord - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Gaspésie / Enfants de 0 à 5 ans et leurs Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Mauricie-et-du-Centre-du-Québec - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Centre - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Est - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Ouest - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Lanaudière - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Laval - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Îles - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Laurentides - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Terres-Cries-de-la-Baie-James - Community Health and Social Services Network (CHSSN) (2016)

Profil sociodémographique des enfants de 0 à 5 ans et de leurs parents RTS de l'Estrie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Le développement de la petite enfance (DPE), est une pierre angulaire du développement humain et l’enfance, est considérée comme étant la phase de développement la plus importante de la durée de la vie d’un individu. Les résultats en matière de développement à ce premier stade de la vie affectent le niveau de santé et de bien-être dont jouit une population dans son devenir. Le développement de la petite enfance est un déterminant social de la vie des communautés et il s’agit d’un processus qui est particulièrement sensible à des déterminants sociaux tels que la situation socioéconomique des familles avec des enfants de 0 à 5 ans et leur environnement social, l’accès aux services sociaux et de santé, la compétence en communication et l’alphabétisation ainsi que l’accès aux réseaux locaux de soutien social.

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Sud-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Est-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Lanaudiére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS du Nord-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

KIDS Summer Camp - Keats, Shannon A. (Coasters Association, 2015)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010, 2011 and 2012, 2013, 2014, 2015 the five camps were in operation and ran very well.

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

2014 K.I.D.S Summer Camp - Keats, Shannon A. (Coasters Association, 2014)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010, 2011 and 2012, 2013, the five camps were in operation and ran very well.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

2013 K.I.D.S Summer Camp - Keats, Shannon A. (Coasters Association, 2013)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010, 2011 and 2012, the five camps were in operation and ran very well.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QCGN Marks End of Notre Home Tour with Benefit Concert for Kids Help Phone - Quebec Community Groups Network (QCGN) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

2012 K.I.D.S Summer Camp - Fequet, Shelley (Coasters Association, 2012)
In the summer of 2006, a six (6) week summer camp pilot project was undertaken in the Municipalities of Bonne Esperance and St. Augustine to provide a Summer Camp for youth. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS”, has proven to be a great success. The mission of KIDS Summer Camp is to nurture and develop a safe and healthy environment in which youth can improve their health and obtain skills that will assist them in their future lives, through physical activities, mental development, artistic growth, environment awareness and community/family participation. In 2007, the Coasters Association expanded the KIDS Summer Camp to two (2) additional communities (La Tabatiere, and Blanc Sablon), as well worked in partnership with, and supported, the Eau-Naturelle Discovery Camp in Chevery, and the two (2) camps already established were maintained. In 2008, 2009, 2010 and 2011 the five camps were in operation and ran very well.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

Wild Berrylicious : Youth School Kit - Coasters Association (2012)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

[La religion en éducation pour les enfants] - McDaid, Mary (2011)

[Religion in Early Childhood Education Facilities and Daycare] - McDaid, Mary (2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

Directives on Daycares - The English Speaking Catholic Council (ESCC) (2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

2011 KIDS Summer Camp - Fequet, Shelley (Coasters Association, 2011)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

2010 KIDS Summer Camp - Thomas, Jenny (Coasters Association, 2010)
Each year the KIDS Summer Camps accommodates the youth and parents in five (5) municipalities across the Lower North Shore (Blanc Sablon. St. Paul’s River, St. Augustine, La Tabatiere and the Eau-Naturelle Discovery Camp in Chevery). These camps provide a safe and happy environment, a unique learning experience for all those involved, as well as assist the camp counsellors with leadership skills that will help them in their future endeavours. It is a place where youth can interact with other youth in an adventurous, natural and spiritual environment. Therefore, the continuation and expansion of the KIDS Summer Camp is an important service to the population of the Lower North Shore.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2010)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2009)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2009)

Kids Summer Camp Report - Thomas, Jenny (Coasters Association, 2009)
Each year KIDS Summer Camps accommodates the youth and parents in five (5) municipalities across the Lower North Shore (Blanc Sablon. St. Paul’s River, St. Augustine, La Tabatiere and the Eau-Naturelle Discovery Camp in Chevery). These camps provide a safe and happy environment, a unique learning experience for all those involved, as well as assist the camp counsellors with leadership skills that will help them in their future endeavors. It is a place where youth can interact with other youth in an adventurous, natural and spiritual environment. Therefore, the continuation and expansion of the KIDS Summer Camp is an important service to the population of the Lower North Shore.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2009)

Kids Summer Camp - Newcombe, Vanessa (Coasters Association, 2008)
The KIDS Summer Camp has been in operation since 2006 and has provided a summer retreat for over 200 youth in five (5) communities, (Blanc Sablon, St. Paul’s River, St. Augustine, La Tabatiere as well as the Eau-Naturelle Discovery Camp in Chevery) thus, accommodating the youth and parents in the five (5) municipalities across the Lower North Shore. Furthermore it provides a vital service to the parents who have no other option but leave the coast for 3 to 4 months out of a year to seek employment elsewhere.

Kids Summer Camp - Newcombe, Vanessa (Coasters Association, 2007)
In the summer of 2006, we embarked on a six (6) week summer camp pilot project in the Municipalities of Bonne Esperance and St. Augustine to provide a Youth Summer Camp for children between the ages of six to twelve. The summer camp entitled Kindness, Inspiration, Determination, Spirit, “KIDS” has proven to be a great success. This year the goal was to expand our efforts to include the communities of Chevery, La Tabatiere, and Blanc Sablon, as well as to continuing the camps already established (St. Augustine, St. Paul’s River).